Different generalizations of the elderly in design of welfare technology - Ertner, Marie (STS Encounters, 2016)
This article explores problems of representing the elderly in a User Driven Innovation (UDI) project developing welfare technology. Drawing on Helen Verran’s concept of the dual logics of generalization I attend to differences in enactments of the elderly. I engage with situations where the objects we study do not seem to ‘fit’ with the categories available or when they seem ‘more than one, but less than many’, and I relate these issues to two different logics of generalization. The contribution of the paper to design studies, and designers who experience difficulties inscribing the elderly into design, is that it shows how Science and Technology Studies (STS) can be useful in order to better recognize differences between different enactments of an imagined user, in this case the elderly. The contribution of the paper to STS is a discussion of how I as an STS-informed ethnographer was invited to participate in a user driven innovation project. Based on my reflections on this role, the paper reflects on the ethnographic account as a tool with particular qualities and limitations when inhabiting a position as mediator between users and an innovation project.